2021
DOI: 10.3390/ijerph182312662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Self-Regulated Training Program on the Repeated Power in Female College Handball Players: An Intervention Study

Abstract: Several resistance training programs using conventional methodologies have been implemented with the purpose of improving the ability to perform power actions in handball, especially during the competitive season. In contrast, methodologies based on a contemporary perspective, which considers the human being as a self-regulating biological entity, and designed specifically for female college players, are scarce. The aim of this research was to investigate the effects of an eight-week resistance training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…In this regard, previous studies have conducted different protocols that may be helpful for improving IR ROM in overhead throwing athletes [ 42 , 43 ]. In addition, previous studies also showed that self-regulated training and non-linear pedagogy in handball can improve running speed and jump height as well as motor skill [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies have conducted different protocols that may be helpful for improving IR ROM in overhead throwing athletes [ 42 , 43 ]. In addition, previous studies also showed that self-regulated training and non-linear pedagogy in handball can improve running speed and jump height as well as motor skill [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los efectos de un programa de entrenamiento autorregulado sobre la potencia repetida (Espoz-Lazo et al, 2021), implementa programas que utilizan metodologías convencionales con el propósito de mejorar la habilidad para realizar acciones de potencia, especialmente durante la temporada competitiva. En cambio, son escasas las metodologías basadas en una perspectiva contemporánea, que considera al ser humano como un ente biológico autorregulador.…”
Section: Introductionunclassified